The water use efficiency of maize depending on abiotic stress factors in field experiments - Csajbók, József; Kutasy, Erika; Pepó, Péter (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2014)
There is little direct information about the effects of the abiotic stress factors such as low soil water content on the photosynthesis system of field crops. Some recent publications pay attention to this field of research. Water stress has significant effect on the yield and other agronomic parameters of maize. The aim of our work was to get more data about the relations between water supply and the assimilation parameters. The photosynthetic gas exchange parameters of maize are remarkably improved by nutrient supply in well watered conditions. The water stress through decreased stomatal conductance has significant negative effect on the assimilation parameters of the crops. The obtained results suggest that the water use efficiency of the maize is higher in dry conditions. In well water supply state maize uses up to 300 per cent more water for 1 g CO2 assimilation.
Keywords: maize; water use efficiency; abiotic stress